41(x-6)+4=6x-8

Simple and best practice solution for 41(x-6)+4=6x-8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 41(x-6)+4=6x-8 equation:


Simplifying
41(x + -6) + 4 = 6x + -8

Reorder the terms:
41(-6 + x) + 4 = 6x + -8
(-6 * 41 + x * 41) + 4 = 6x + -8
(-246 + 41x) + 4 = 6x + -8

Reorder the terms:
-246 + 4 + 41x = 6x + -8

Combine like terms: -246 + 4 = -242
-242 + 41x = 6x + -8

Reorder the terms:
-242 + 41x = -8 + 6x

Solving
-242 + 41x = -8 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
-242 + 41x + -6x = -8 + 6x + -6x

Combine like terms: 41x + -6x = 35x
-242 + 35x = -8 + 6x + -6x

Combine like terms: 6x + -6x = 0
-242 + 35x = -8 + 0
-242 + 35x = -8

Add '242' to each side of the equation.
-242 + 242 + 35x = -8 + 242

Combine like terms: -242 + 242 = 0
0 + 35x = -8 + 242
35x = -8 + 242

Combine like terms: -8 + 242 = 234
35x = 234

Divide each side by '35'.
x = 6.685714286

Simplifying
x = 6.685714286

See similar equations:

| 9x+7(3x-4)=7-5x | | 4x-2(x-3)=-5+4x+1 | | 9v-9=3(v-5) | | 2x^2+x^2=25*25 | | 4-2(x-3)=5+4x+1 | | 4x-15=x+51 | | 0.5x+9= | | 208=-13 | | 12x^3+28x^2+13x-45=0 | | 3x+10=7x-5 | | 25x^4-50x^3+25x^2=0 | | 8y+2=4x | | 3x+20=41 | | X+(-3)+9=-1+14 | | h(t)=-4.9t^2+24t+8 | | 4x^7-32x^5= | | 34+20=41 | | 2x-38=180 | | x^2+24-11x= | | 27=7+4w | | e^10x+6=12 | | 9a+27= | | 17=-5m+3 | | 5(y+4)=8y-45 | | 4x+7x-38=76-8x | | 3a+2w-5a-9w= | | 7+24m=28+17m | | 8x-3y=37 | | 16x^4-16x^3+4x^2=0 | | 5x^7-35x^5= | | 50+33=2a-44 | | 4x+8+5x+1=90 |

Equations solver categories